KEPEMIMPINAN, KREATIVITAS DAN KECAKAPAN HIDUP - W. P. Napitupulu (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
A country and her people could be well developed if there are available enough qualified human resources which are produced by educational institutions. This article discusses leadership, creativity, and life skills which are very important for human survival. The success of an organization to sustain and develop is much depends on the leadership practiced by the leaders within the organization. While individual or group creativity is required to find innovative solutions to overcome the problems effectively and efficiently. Finally, life skills are needed by everybody to enable him/her to survive successfully. The roles of education in developing leadership, creativity, and life skills are put forwards thoroughly.